SUBSTITUTION OF ARTEMIA WITHBRACHIONUS IN DIFFERENT RATIOS DURING LARVAL REARING OF MACROBRACHIUM ROSENBERG/I AND EVALUATION OF THEIR FEED EFFICACY - DAS, APURBA KUMAR; MOHIUDDIN, M. IFTEKHAR (Journal of Indian Fisheries Association, 2016)
Larval growth during stage I-VIll were studied inMacrobrachium rosenbergii.Duration in moult periodicity were recorded-during larval development period,larvae were fed withBrachionus (grown on Baker's yeast and also Brachinousraised through organic manuring in outdoor culture containers). Theperformance of the feed was evaluated through substitution of brachionus inthe feeding protocol, in lieu of artemia 1st instar. The Artemia, Br~chionussubstition ratio of 75:25 was found to be most efficient.The study also indicates that the comparative growth rate of Brachionusplicatilis is higher in manure loaded tanks than with Baker's yeast. Growthrate "Y'' in culture tank being 0.245 and 0.112 and corresponding duplicatingtime (Td) too was found to be 2.855 and 6.365 respectively in tanks manured/enriched with pig manure.Keywords: Feeding efficacy, Substitution ratio,Artemia/Brachionus